Outcomes of the care system for older people with chronic disease by volunteer process - Nokham , Ranchana; Kitisri , Chutamat; Chaiwong , Punnee; Unuai , Kannika; Mongkhonittivech , Nongyao (Nursing Journal CMU, 2020)
The older people with chronic disease tend to increase and need continuing care at home. The Health care service has expanded therefor more into communities. This research aimed to study the outcome of care system for older people with chronic disease through volunteer process. The samples selected by purposive sampling were 22 older persons, 22 caregivers, and 22 volunteers. The instruments of this study composed of 1) The short format Thai Mental Health Indicators (TMHI) 2) The quality WHO of life assessment instrument (WHOQOL-Brief) 3) The satisfaction evaluation form on the care system for older people with chronic was developed by the researcher. Data were analyzed using descriptive statistics and paired t-test. The result of this research showed that after the development of a care system for older people with chronic disease through volunteers. The quality of life, happiness and satisfaction of the elderly were significantly higher (p<0.001). Elderly caregivers were significantly more satisfied (p <0.05). The happiness and satisfaction of the volunteers were significantly higher (p<0.001). The results of this study can be used to provide a care system of elderly with chronic disease through volunteers in the community. To enhance the elderly, do activity daily living according to their potential. Having a happiness and good quality of life. And a guideline for use a chronic care system for older people in other community.